Modified mirror concrete and preparation method thereof

By adding modified epoxy resin and modified polypropylene fiber, the problems of insufficient impact resistance and poor UV resistance of mirror concrete in scenarios with high traffic and high mechanical impact loads are solved, achieving high durability and low-cost industrial application of mirror concrete.

CN120463470BActive Publication Date: 2025-09-19THE 2ND ENG CO LTD OF CHINA RAILWAY URBAN CONSTR GRP +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510970728.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-07-15
Publication Date
2025-09-19
Estimated Expiration
2045-07-15

AI Technical Summary

Technical Problem

Mirror concrete has insufficient impact resistance in scenarios with high traffic and high mechanical impact loads, and its UV resistance is poor, which affects its service life.

Method used

By increasing the addition ratio of fiber and resin, modified epoxy resin and modified polypropylene fiber are used to improve the impact resistance and UV resistance of mirror concrete. The modification process includes the esterification reaction of 2,4-diaminophenol and m-aminobenzoic acid to prepare a UV absorber, and intercalation with bentonite to prepare modified polypropylene fiber, which is cross-linked by a silane coupling agent-modified ZnO/TiO2 nanocomposite.

Benefits of technology

The impact resistance and durability of mirror concrete are improved, the interface bonding strength between fiber and resin is enhanced, the compressive strength is improved, the raw material cost is reduced, and it is easy to apply in industry.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention provides a modified mirror concrete and a preparation method thereof, belonging to the field of concrete technology. The modified mirror concrete comprises the following raw materials, by weight: 90-150 parts of a water-based modified epoxy resin, 270-320 parts of cement, 500-600 parts of coarse aggregate, 700-800 parts of fine aggregate, 20-40 parts of silica fume, 40-60 parts of fly ash, 3-7 parts of a polycarboxylate water-reducing agent, 10-15 parts of modified polypropylene fiber, and 120-180 parts of water. The modified mirror concrete prepared by the present invention increases the addition ratio of fiber and resin, thereby improving the mirror effect. Furthermore, the modified mirror concrete has good UV resistance and impact resistance, and improves the durability and weather resistance of the concrete. Furthermore, the raw material cost is low, and it is easy to implement industrial applications, thus having broad application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of concrete, and in particular to a modified mirror concrete and a preparation method thereof. Background Art

[0002] Mirror concrete is a high-gloss decorative concrete material with a mirror-smooth surface. Through formwork texture design, it can achieve visual effects such as stone and metal. It also possesses the mechanical properties of concrete. In recent years, it has been widely used in floors and walls of public spaces such as commercial complexes. However, in order to achieve better decorative effects, mirror concrete requires reducing the particle size and proportion of coarse aggregate. This directly leads to a weakening of the fiber bridging effect within the mirror concrete, a decrease in crack propagation resistance, and an increase in brittleness. In scenes with high traffic and high mechanical impact loads such as shopping malls, the impact resistance defects of mirror concrete are gradually exposed. Damage caused by frequent rolling of shopping carts / luggage boxes, falling heavy objects (such as shelf goods and equipment), and trampling by dense passenger flow has seriously reduced the service life of mirror concrete. This has also become a key technical bottleneck restricting the use of mirror concrete in such high-traffic scenes.

[0003] Epoxy resin is a thermosetting resin with a wide range of applications and excellent bonding properties. Using epoxy resin to partially replace silicate cement can effectively improve the mechanical properties of mirror concrete. However, epoxy resin has poor resistance to UV aging. After aging under the influence of ultraviolet rays, epoxy resin will not only turn yellow and affect the visual effect, but the toughness of epoxy resin will also decrease. Adding ultraviolet absorbers can improve the ultraviolet resistance of epoxy resin, but the service life of concrete is long. As time goes by, the ultraviolet absorbers in the concrete may migrate or decompose, thereby losing their protective effect.

[0004] In order to solve the above technical defects, it is necessary to prepare a mirror concrete with good impact resistance, UV resistance and aging resistance. Summary of the Invention

[0005] The purpose of the present invention is to propose a modified mirror concrete and a preparation method thereof, which increases the addition ratio of fiber and resin, improves the mirror effect, and at the same time has good UV resistance and impact resistance, improves the durability and weather resistance of concrete, and has low raw material cost, is easy to realize industrial application, and has broad application prospects.

[0006] The technical solution of the present invention is achieved as follows:

[0007] The invention provides a modified mirror concrete, which comprises the following raw materials in parts by weight: 90-150 parts of water-based modified epoxy resin, 270-320 parts of cement, 500-600 parts of coarse aggregate, 700-800 parts of fine aggregate, 20-40 parts of silica fume, 40-60 parts of fly ash, 3-7 parts of polycarboxylic acid water-reducing agent, 10-15 parts of modified polypropylene fiber, and 120-180 parts of water. The water-based modified epoxy resin is prepared by esterifying 2,4-diaminophenol and m-aminobenzoic acid, performing Fries rearrangement, intercalating bentonite, and mixing the mixture with water-based epoxy resin emulsion. The modified polypropylene fiber is prepared by polymerizing and cross-linking maleic anhydride-grafted polypropylene and a silane coupling agent-modified ZnO / TiO2 nanocomposite.

[0008] As a further improvement of the present invention, the preparation method of the water-based modified epoxy resin is as follows:

[0009] S1. 2,4-diaminophenol and m-aminobenzoic acid are dissolved in an organic solvent, a catalyst is added, and the reaction is heated under reflux with stirring to obtain an ester;

[0010] S2. The esterified product was dissolved in polyphosphoric acid, heated and stirred to obtain a curable UV absorber;

[0011] S3. The bentonite was added to water, a curing UV absorber was added, and the intercalation was stirred to obtain a modified curing agent;

[0012] S4. The epoxy resin, diethanolamine, ethyl bromide were stirred and mixed, heated and evaporated, and the pH value was adjusted with acetic acid to obtain an epoxy resin emulsion;

[0013] S5. The epoxy resin emulsion and the epoxy resin were added to water and the solid content was adjusted to obtain an epoxy resin emulsion;

[0014] S6. When preparing the modified mirror concrete, the epoxy resin emulsion and the modified curing agent are evenly mixed to prepare a water-based modified epoxy resin, which is added to other raw materials for further subsequent preparation.

[0015] As a further improvement of the present invention, the mass ratio of 2,4-diaminophenol, m-aminobenzoic acid, and catalyst in step S1 is 11.2-13.6:12.3-15.1:0.1-0.9, the catalyst is p-toluenesulfonic acid, and the heating reflux stirring reaction time is 4-6 hours; the polyphosphoric acid in step S2 is a polyphosphoric acid with a phosphorus pentoxide content of 76-85%.

[0016] As a further improvement of the present invention, the mass ratio of the bentonite to the curing ultraviolet absorber in step S3 is 10:2-3; and the mass ratio of the epoxy resin, diethanolamine, and ethyl bromide in step S4 is 10-15:3-6:1-3.

[0017] As a further improvement of the present invention, the mass ratio of the epoxy resin emulsion and the epoxy resin in step S5 is 3-5:13-16, and the adjusted solid content is 45-55%; the mass ratio of the epoxy resin emulsion and the modified curing agent in step S6 is 10:4-6.

[0018] As a further improvement of the present invention, the preparation method of the modified polypropylene fiber is as follows:

[0019] T1 maleic anhydride grafted modified polypropylene: maleic anhydride, polypropylene, and an initiator were added to an internal mixer, heated and stirred to blend, the product was removed, and dried to obtain maleic anhydride grafted modified polypropylene;

[0020] T2. Preparation of ZnO / TiO2 nanocomposites: Zinc acetate and tetrabutyl titanate were dissolved in ethanol, citric acid and water were added, the pH of the solution was adjusted, the reaction was stirred, centrifuged, washed, dried, and calcined to obtain a ZnO / TiO2 nanocomposite.

[0021] T3. Preparation of modified ZnO / TiO2 nanocomposites: The ZnO / TiO2 nanocomposites were added to an ethanol aqueous solution, a composite silane coupling agent was added, the mixture was heated and stirred, the reaction was centrifuged, washed, and dried to obtain a modified ZnO / TiO2 nanocomposite;

[0022] T4. Maleic anhydride grafted modified polypropylene, modified ZnO / TiO2 nanocomposite, divinylbenzene, and initiator were added to an internal mixer, heated and stirred to react, and the product was removed and dried to obtain modified polypropylene fiber.

[0023] As a further improvement of the present invention, the mass ratio of maleic anhydride, polypropylene, and initiator in step T1 is 3-5:15-20:0.05-0.1, the temperature of the heating and stirring blending is 160-170°C, the time is 4-6 hours, and the initiator is benzoyl peroxide; the mass ratio of zinc acetate, tetrabutyl titanate, and citric acid in step T2 is 2-4:3-7:3-5, the pH value of the solution is adjusted to 5-6, the stirring reaction time is 3-5 hours, and the calcination temperature is 450-550°C, and the time is 2-4 hours.

[0024] As a further improvement of the present invention, the mass ratio of the ZnO / TiO2 nanocomposite and the composite silane coupling agent in step T3 is 10:2-3, the composite silane coupling agent includes KH602 and KH570 in a mass ratio of 3-5:2-4, the temperature of the heating and stirring reaction is 40-50°C, and the time is 2-3h; the mass ratio of the maleic anhydride grafted modified polypropylene, modified ZnO / TiO2 nanocomposite, divinylbenzene and initiator in step T4 is 18-22:3-5:0.5-1:0.05-0.1, the initiator is benzoyl peroxide, the temperature of the heating and stirring reaction is 160-170°C, and the time is 2-3h.

[0025] As a further improvement of the present invention, the coarse aggregate is basalt with a particle size of 5-10 mm, the fine aggregate is machine-made sand with a fineness modulus of 2.3-2.9 and a mud content of 0.3-1%; and the cement is silicate cement with a PO4 of 2.5.

[0026] The method for preparing the modified mirror concrete prepared by the present invention comprises the following steps:

[0027] Weigh the raw materials according to their mass fractions, mix cement, coarse aggregate, fine aggregate, fly ash, silica fume and modified polypropylene fiber, add 40-60% of the water in the raw materials, stir for 2-4 minutes, then add water-based modified epoxy resin, polycarboxylate water reducer and all the remaining water in the raw materials to the system, continue stirring for 2-4 minutes, pour, vibrate and compact, remove the formwork 48-72 hours after the pouring is completed, and cure to obtain impact-resistant modified mirror concrete;

[0028] The water-based modified epoxy resin is prepared by uniformly mixing the epoxy resin emulsion and the modified curing agent 10-15 minutes in advance.

[0029] The present invention has the following beneficial effects:

[0030] The present invention uses 2,4-diaminophenol and m-aminobenzoic acid as raw materials. The hydroxyl groups of 2,4-diaminophenol and the carboxyl groups of m-aminobenzoic acid undergo an esterification reaction under the catalysis of p-toluenesulfonic acid to produce an esterified product with an amino group. This product then undergoes a Fries rearrangement reaction under the catalysis of polyphosphoric acid to produce a cured UV absorber. This product is then intercalated into bentonite, improving UV absorption performance and preventing material aging, discoloration, and performance degradation due to UV exposure. The dispersibility of the cured UV absorber in inorganic cement systems is also improved, while migrating or decomposing the cured UV absorber, which can lead to loss of its protective effect, and improving the mechanical properties of the epoxy resin. The resulting epoxy resin emulsion is then evenly mixed with a modified curing agent to produce a water-based modified epoxy resin with good water solubility, low VOC emissions, and environmental friendliness.

[0031] The present invention prepares a modified polypropylene fiber. Maleic anhydride monomer is grafted onto a polypropylene molecular chain by a solid-phase grafting method. Maleic anhydride can be used as a compatibilizer to improve the compatibility and impact resistance of polypropylene with other water-based modified epoxy resins or fillers. In addition, a ZnO / TiO2 nanocomposite is prepared through a sol-gel reaction. The composite has good ultraviolet absorption and scattering properties, reduces the influence of ultraviolet rays on the resin, thereby increasing the addition amount of polypropylene fiber and epoxy resin in cement and improving the impact resistance. In addition, the present invention modifies the ZnO / TiO2 nanocomposite by using a silane coupling agent with a double bond and a silane coupling agent with an amino group. On the one hand, the modified ZnO / TiO2 nanocomposite, maleic anhydride grafted polypropylene, and a crosslinking reaction with the assistance of a crosslinking auxiliary agent such as divinylbenzene can avoid chain scission degradation reaction of the polypropylene main chain, ensure an ideal crosslinking effect, improve the regularity and interaction of the molecular chain, and thus enhance the toughness and impact resistance of the fiber. On the other hand, the present invention utilizes the property that the amino group easily undergoes a ring-opening reaction with the epoxy group. The prepared modified polypropylene fiber can react with the water-based epoxy resin to form a chemical bond, significantly improving the interface bonding strength between the modified polypropylene fiber and the epoxy resin matrix, reducing stress concentration, and improving the overall compressive strength and impact resistance of the mirror concrete.

[0032] The curable UV absorber of the present invention has an ortho-hydroxybenzophenone structure. This type of conjugated UV absorber has a good absorption effect on medium and long-wave ultraviolet rays (280-340 nm). The amino structure in the UV absorber has the formula: UV absorber-NH2+CH2-CH(O)-OR→UV absorber-NH-CH2-CH(OH)-OR, wherein R represents the main chain skeleton of the epoxy resin, the amino group (-NH2), the secondary amine bond NH-CH, and the hydroxyl group CH(OH). After reacting and curing with the epoxy group in the epoxy resin, the UV absorber not only enhances the light decomposition resistance of the UV absorber, but also enhances the stability of the conjugated system through the electron donation effect, increases the effective wavelength range of the UV absorber, and enhances the absorption effect on long-wave ultraviolet rays (320-400 nm).

[0033] The modified mirror concrete prepared by the present invention increases the addition ratio of fiber and resin, improves the mirror effect, and at the same time has good ultraviolet resistance and impact resistance, improves the durability and weather resistance of the concrete, and has low raw material cost, is easy to realize industrial application, and has broad application prospects. DETAILED DESCRIPTION

[0034] The following is a clear and complete description of the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts are within the scope of protection of the present invention.

[0035] Preparation Example 1 Preparation of water-based modified epoxy resin

[0036] Here’s how:

[0037] S1. 11.2 g of 2,4-diaminophenol and 12.3 g of m-aminobenzoic acid were dissolved in 500 mL of toluene, 0.1 g of p-toluenesulfonic acid was added, and the reaction was stirred under reflux for 4 h to obtain an ester;

[0038] S2. 20 g of the ester was dissolved in 100 mL of polyphosphoric acid, heated to 100 ° C, and stirred for 3 h to obtain a curable UV absorber;

[0039] S3 10g of bentonite was added to 150mL of water, 2g of curing UV absorber was added, and the intercalation was stirred for 30min to obtain a modified curing agent;

[0040] S4 10g of epoxy resin E51, 3g of diethanolamine, and 1g of ethyl bromide were stirred and mixed, heated to 80 ° C for evaporation, and the pH value was adjusted to 6 with acetic acid to obtain an epoxy resin emulsion;

[0041] S5 3g of epoxy resin emulsion and 13g of epoxy resin E51 were added to water and the solid content was adjusted to 45% to obtain an epoxy resin emulsion;

[0042] S6. When preparing the modified mirror concrete, 10 g of epoxy resin emulsion and 4 g of modified curing agent were mixed evenly to prepare a water-based modified epoxy resin, which was added to other raw materials for further preparation.

[0043] Preparation Example 2 Preparation of water-based modified epoxy resin

[0044] Here’s how:

[0045] S1. 13.6 g of 2,4-diaminophenol and 15.1 g of m-aminobenzoic acid were dissolved in 500 mL of toluene, 0.9 g of p-toluenesulfonic acid was added, and the reaction was stirred under reflux for 6 h to obtain an ester;

[0046] S2. 20 g of the ester was dissolved in 100 mL of polyphosphoric acid, heated to 130 ° C, and stirred for 8 h to obtain a curable UV absorber;

[0047] S3 10g of bentonite was added to 150mL of water, 3g of curing UV absorber was added, and the intercalation was stirred for 30min to obtain a modified curing agent;

[0048] S4 15g of epoxy resin E51, 6g of diethanolamine, 3g of ethyl bromide were stirred and mixed, heated to 80 ° C for evaporation, and the pH value was adjusted to 6.5 with acetic acid to obtain an epoxy resin emulsion;

[0049] S5 5g of epoxy resin emulsion and 16g of epoxy resin E51 were added to water and the solid content was adjusted to 55% to obtain an epoxy resin emulsion;

[0050] S6. When preparing modified mirror concrete, 10 g of epoxy resin emulsion and 6 g of modified curing agent were mixed evenly to prepare a water-based modified epoxy resin, which was added to other raw materials for further subsequent preparation.

[0051] Preparation Example 3 Preparation of water-based modified epoxy resin

[0052] Here’s how:

[0053] S1. 12 g of 2,4-diaminophenol and 13.5 g of m-aminobenzoic acid were dissolved in 500 mL of toluene, 0.5 g of p-toluenesulfonic acid was added, and the reaction was stirred under reflux for 5 h to obtain an ester.

[0054] S2. 20 g of the ester was dissolved in 100 mL of polyphosphoric acid, heated to 115 ° C, and stirred for 5 h to obtain a curable UV absorber;

[0055] S3 10g of bentonite was added to 150mL of water, 2.5g of curing UV absorber was added, and the intercalation was stirred for 30min to obtain a modified curing agent;

[0056] S4 12g of epoxy resin E51, 4.5g of diethanolamine, 2g of ethyl bromide were stirred and mixed, heated to 80 ° C for evaporation, and the pH value was adjusted to 6.2 with acetic acid to obtain an epoxy resin emulsion;

[0057] S5 4g of epoxy resin emulsion and 14.5g of epoxy resin E51 were added to water and the solid content was adjusted to 50% to obtain an epoxy resin emulsion;

[0058] S6. When preparing the modified mirror concrete, 10 g of epoxy resin emulsion and 5 g of modified curing agent were mixed evenly to prepare a water-based modified epoxy resin, which was added to other raw materials for further subsequent preparation.

[0059] Comparative Preparation Example 1

[0060] Compared with Preparation Example 3, the difference is that step S2 is not performed.

[0061] The details are as follows:

[0062] S1. 12 g of 2,4-diaminophenol and 13.5 g of m-aminobenzoic acid were dissolved in 500 mL of toluene, 0.5 g of p-toluenesulfonic acid was added, and the reaction was stirred under reflux for 5 h to obtain an ester.

[0063] S2 10g of bentonite was added to 150mL of water, 2.5g of ester was added, and the intercalation was stirred for 30min to obtain a modified curing agent;

[0064] S3 12g of epoxy resin E51, 4.5g of diethanolamine, 2g of ethyl bromide were stirred and mixed, heated to 80 ° C for evaporation, and the pH value was adjusted to 6.2 with acetic acid to obtain an epoxy resin emulsion;

[0065] S4 4g of epoxy resin emulsion and 14.5g of epoxy resin E51 were added to water and the solid content was adjusted to 50% to obtain an epoxy resin emulsion;

[0066] S5. When preparing the modified mirror concrete, 10 g of epoxy resin emulsion and 5 g of modified curing agent were mixed evenly to prepare a water-based modified epoxy resin, which was added to other raw materials for further subsequent preparation.

[0067] Comparative Preparation Example 2

[0068] Compared with Preparation Example 3, the difference is that step S3 is not performed.

[0069] The details are as follows:

[0070] S1. 12 g of 2,4-diaminophenol and 13.5 g of m-aminobenzoic acid were dissolved in 500 mL of toluene, 0.5 g of p-toluenesulfonic acid was added, and the reaction was stirred under reflux for 5 h to obtain an ester.

[0071] S2. 20 g of the ester was dissolved in 100 mL of polyphosphoric acid, heated to 115 ° C, and stirred for 5 h to obtain a curable UV absorber;

[0072] S3 12g of epoxy resin E51, 4.5g of diethanolamine, 2g of ethyl bromide were stirred and mixed, heated to 80 ° C for evaporation, and the pH value was adjusted to 6.2 with acetic acid to obtain an epoxy resin emulsion;

[0073] S4 4g of epoxy resin emulsion and 14.5g of epoxy resin E51 were added to water and the solid content was adjusted to 50% to obtain an epoxy resin emulsion;

[0074] S5. When preparing modified mirror concrete, 10 g of epoxy resin emulsion and 5 g of curing UV absorber were mixed evenly to prepare a water-based modified epoxy resin, which was added to other raw materials for further subsequent preparation.

[0075] Preparation Example 4 Preparation of modified polypropylene fiber

[0076] Here’s how:

[0077] T1. Maleic anhydride grafted polypropylene: 3g of maleic anhydride, 15g of polypropylene, and 0.05g of benzoyl peroxide were added to an internal mixer, heated to 160°C, and stirred for 4h. The product was removed and dried to obtain maleic anhydride grafted polypropylene.

[0078] T2. Preparation of ZnO / TiO2 nanocomposites: 2 g of zinc acetate and 3 g of tetrabutyl titanate were dissolved in 200 mL of ethanol. 3 g of citric acid and 20 mL of water were added, and the pH of the solution was adjusted to 5. The reaction was stirred for 3 h, centrifuged, washed, dried, and calcined at 450°C for 2 h to produce a ZnO / TiO2 nanocomposite.

[0079] T3. Preparation of modified ZnO / TiO2 nanocomposites: 10 g of ZnO / TiO2 nanocomposites were added to 200 mL of 70 wt% aqueous ethanol solution, followed by 2 g of a composite silane coupling agent. The mixture was heated to 40°C and stirred for 2 h. The mixture was centrifuged, washed, and dried to obtain a modified ZnO / TiO2 nanocomposite.

[0080] The composite silane coupling agent includes KH602 and KH570 in a mass ratio of 3:2;

[0081] T4. Add 18g of maleic anhydride-grafted modified polypropylene, 3g of modified ZnO / TiO2 nanocomposite, 0.5g of divinylbenzene, and 0.05g of benzoyl peroxide to an internal mixer. Heat to 160°C and stir for 2h. Remove the product and dry it to obtain modified polypropylene fiber.

[0082] Preparation Example 5 Preparation of modified polypropylene fiber

[0083] Here’s how:

[0084] T1. Maleic anhydride grafted polypropylene: 5 g of maleic anhydride, 20 g of polypropylene, and 0.1 g of benzoyl peroxide were added to an internal mixer, heated to 170°C, and stirred for 6 h. The product was removed and dried to obtain maleic anhydride grafted polypropylene.

[0085] T2. Preparation of ZnO / TiO2 nanocomposites: 4 g of zinc acetate and 7 g of tetrabutyl titanate were dissolved in 200 mL of ethanol. 5 g of citric acid and 20 mL of water were added, and the pH of the solution was adjusted to 6. The reaction was stirred for 5 h, centrifuged, washed, dried, and calcined at 550°C for 4 h to produce a ZnO / TiO2 nanocomposite.

[0086] T3. Preparation of modified ZnO / TiO2 nanocomposites: 10 g of ZnO / TiO2 nanocomposites were added to 200 mL of 70 wt% aqueous ethanol solution, followed by 3 g of a composite silane coupling agent. The mixture was heated to 50°C and stirred for 3 h. The mixture was centrifuged, washed, and dried to obtain a modified ZnO / TiO2 nanocomposite.

[0087] The composite silane coupling agent includes KH602 and KH570 in a mass ratio of 5:4;

[0088] T4. Add 22g of maleic anhydride-grafted modified polypropylene, 5g of modified ZnO / TiO2 nanocomposite, 1g of divinylbenzene, and 0.1g of benzoyl peroxide to an internal mixer. Heat to 170°C and stir for 3h. Remove the product and dry it to obtain modified polypropylene fiber.

[0089] Preparation Example 6 Preparation of modified polypropylene fiber

[0090] Here’s how:

[0091] T1. Maleic anhydride grafted polypropylene: 4 g of maleic anhydride, 17 g of polypropylene, and 0.07 g of benzoyl peroxide were added to an internal mixer, heated to 165°C, and stirred for 5 h. The product was removed and dried to obtain maleic anhydride grafted polypropylene.

[0092] T2. Preparation of ZnO / TiO2 nanocomposites: 3 g of zinc acetate and 5 g of tetrabutyl titanate were dissolved in 200 mL of ethanol. 4 g of citric acid and 20 mL of water were added, and the pH of the solution was adjusted to 5.5. The mixture was stirred for 4 h, centrifuged, washed, dried, and calcined at 500°C for 3 h to produce a ZnO / TiO2 nanocomposite.

[0093] T3. Preparation of modified ZnO / TiO2 nanocomposites: 10 g of ZnO / TiO2 nanocomposites were added to 200 mL of 70 wt% aqueous ethanol solution, followed by 2.5 g of a composite silane coupling agent. The mixture was heated to 45°C and stirred for 2.5 h. The mixture was centrifuged, washed, and dried to obtain a modified ZnO / TiO2 nanocomposite.

[0094] The composite silane coupling agent includes KH602 and KH570 in a mass ratio of 35:24;

[0095] T4. Add 20g of maleic anhydride-grafted modified polypropylene, 4g of modified ZnO / TiO2 nanocomposite, 0.7g of divinylbenzene, and 0.07g of benzoyl peroxide to an internal mixer. Heat to 165°C and stir for 2.5h. Remove the product and dry it to obtain modified polypropylene fiber.

[0096] Comparative Preparation Example 3

[0097] Compared with Preparation Example 6, the difference is that zinc acetate is not added in step T2.

[0098] The details are as follows:

[0099] T2. Preparation of TiO2 nanocomposite: 8 g of tetrabutyl titanate was dissolved in 200 mL of ethanol, 4 g of citric acid and 20 mL of water were added, and the pH of the solution was adjusted to 5.5. The mixture was stirred for 4 h, centrifuged, washed, dried, and calcined at 500°C for 3 h to obtain a TiO2 nanocomposite.

[0100] Comparative Preparation Example 4

[0101] Compared with Preparation Example 6, the difference is that tetrabutyl titanate is not added in step T2.

[0102] The details are as follows:

[0103] T2. Preparation of ZnO nanocomposites: 8 g of zinc acetate was dissolved in 200 mL of ethanol, 4 g of citric acid and 20 mL of water were added, and the pH of the solution was adjusted to 5.5. The mixture was stirred for 4 h, centrifuged, washed, dried, and calcined at 500°C for 3 h to obtain a ZnO nanocomposite.

[0104] Comparative Preparation Example 5

[0105] Compared with Preparation Example 6, the difference is that step T3 is not performed.

[0106] The details are as follows:

[0107] T1. Maleic anhydride grafted polypropylene: 4 g of maleic anhydride, 17 g of polypropylene, and 0.07 g of benzoyl peroxide were added to an internal mixer, heated to 165°C, and stirred for 5 h. The product was removed and dried to obtain maleic anhydride grafted polypropylene.

[0108] T2. Preparation of ZnO / TiO2 nanocomposites: 3 g of zinc acetate and 5 g of tetrabutyl titanate were dissolved in 200 mL of ethanol. 4 g of citric acid and 20 mL of water were added, and the pH of the solution was adjusted to 5.5. The mixture was stirred for 4 h, centrifuged, washed, dried, and calcined at 500°C for 3 h to produce a ZnO / TiO2 nanocomposite.

[0109] T3. Add 20g of maleic anhydride-grafted modified polypropylene, 4g of ZnO / TiO2 nanocomposite, 0.7g of divinylbenzene, and 0.07g of benzoyl peroxide to an internal mixer. Heat to 165°C and stir for 2.5h. Remove the product and dry it to obtain modified polypropylene fiber.

[0110] Test Example 1

[0111] The water-based modified epoxy resin and the modified polypropylene fiber are evenly mixed and cured to form a cured board.

[0112] Test group 1: water-based modified epoxy resin of Preparation Example 1 + modified polypropylene fiber of Preparation Example 4, with a mass ratio of 60:20.

[0113] Test group 2: water-based modified epoxy resin of Preparation Example 2 + modified polypropylene fiber of Preparation Example 5, with a mass ratio of 60:20.

[0114] Test group 3: water-based modified epoxy resin of Preparation Example 3 + modified polypropylene fiber of Preparation Example 6, with a mass ratio of 60:20.

[0115] Comparative Group 1: Comparative Preparation Example 1 water-based modified epoxy resin + Preparation Example 6 modified polypropylene fiber, mass ratio is 60:20.

[0116] Comparative Group 2: Comparative Preparation Example 2 water-based modified epoxy resin + Preparation Example 6 modified polypropylene fiber, mass ratio is 60:20.

[0117] Comparative Group 3: Water-based modified epoxy resin of Preparation Example 3 + modified polypropylene fiber of Comparative Preparation Example 3, with a mass ratio of 60:20.

[0118] Comparative Group 4: Water-based modified epoxy resin of Preparation Example 3 + modified polypropylene fiber of Comparative Preparation Example 4, with a mass ratio of 60:20.

[0119] Comparative Group 5: Water-based modified epoxy resin of Preparation Example 3 + modified polypropylene fiber of Comparative Preparation Example 5, with a mass ratio of 60:20.

[0120] Control group: polypropylene fiber + ultraviolet absorber UV-0 + water-based epoxy resin + curing agent hexamethylenediamine, the mass ratio is 20:1:34:15.

[0121] The cured boards were subjected to UV aging resistance tests, where the aging conditions were UV wavelength (280-400nm) and aging temperature 40°C. The impact strength of the cured boards after aging for 400h and 1000h was tested respectively. The initial impact strength was taken as 100%, and the mechanical property retention rate of each component cured board was calculated. The test results are shown in Table 1:

[0122] Table 1

[0123]

[0124] As can be seen from Table 1, compared with the method of directly adding ultraviolet absorbers, the present invention modifies the water-based epoxy resin and mixes it with modified polypropylene for curing, which can better improve the aging resistance of the cured board and has better impact strength after curing.

[0125] Example 1

[0126] This embodiment provides a modified mirror concrete.

[0127] The raw materials include the following by weight: 90 parts of the water-based modified epoxy resin prepared in Preparation Example 1, 270 parts of Portland cement with a PO4 of 2.5, 500 parts of coarse aggregate, 700 parts of fine aggregate, 20 parts of silica fume, 40 parts of fly ash, 3 parts of a polycarboxylate superplasticizer, 10 parts of the modified polypropylene fiber prepared in Preparation Example 4, and 120 parts of water. The coarse aggregate is basalt with a particle size of 5-10 mm, and the fine aggregate is machine-made sand with a fineness modulus of 2.3-2.9 and a mud content of 0.3-1%.

[0128] The preparation method comprises the following steps:

[0129] After weighing each raw material according to mass fraction, cement, coarse aggregate, fine aggregate, fly ash, silica fume and modified polypropylene fiber are mixed, and 40% of the water in the raw materials is added. After stirring for 2 minutes, water-based modified epoxy resin, polycarboxylate water reducer and all the remaining water in the raw materials are added to the system. After stirring for another 2 minutes, pouring and vibrating to compact the concrete. 48 hours after pouring, the formwork is removed and the concrete is cured to obtain impact-resistant modified mirror concrete.

[0130] The water-based modified epoxy resin is prepared by uniformly mixing the epoxy resin emulsion and the modified curing agent 10 minutes in advance.

[0131] Example 2

[0132] This embodiment provides a modified mirror concrete.

[0133] The raw materials include the following by weight: 150 parts of the water-based modified epoxy resin prepared in Preparation Example 2, 320 parts of Portland cement with a PO4 of 2.5, 600 parts of coarse aggregate, 800 parts of fine aggregate, 40 parts of silica fume, 60 parts of fly ash, 7 parts of a polycarboxylate superplasticizer, 15 parts of the modified polypropylene fiber prepared in Preparation Example 5, and 120-180 parts of water. The coarse aggregate is basalt with a particle size of 5-10 mm, and the fine aggregate is machine-made sand with a fineness modulus of 2.3-2.9 and a mud content of 0.3-1%.

[0134] The preparation method comprises the following steps:

[0135] Weigh each raw material according to mass fraction, mix cement, coarse aggregate, fine aggregate, fly ash, silica fume and modified polypropylene fiber, add 60% of the water in the raw materials, stir for 4 minutes, then add water-based modified epoxy resin, polycarboxylate water reducer and all the remaining water in the raw materials to the system, continue stirring for 4 minutes, pour, vibrate and compact, remove the formwork 72 hours after the pouring is completed, and cure and solidify to obtain impact-resistant modified mirror concrete;

[0136] The water-based modified epoxy resin is prepared by uniformly mixing the epoxy resin emulsion and the modified curing agent 15 minutes in advance.

[0137] Example 3

[0138] This embodiment provides a modified mirror concrete.

[0139] The raw materials include the following by weight: 110 parts of the water-based modified epoxy resin prepared in Preparation Example 3, 300 parts of Portland cement with a PO4 of 2.5, 550 parts of coarse aggregate, 750 parts of fine aggregate, 30 parts of silica fume, 50 parts of fly ash, 5 parts of a polycarboxylate superplasticizer, 12 parts of the modified polypropylene fiber prepared in Preparation Example 6, and 120-180 parts of water. The coarse aggregate is basalt with a particle size of 5-10 mm, and the fine aggregate is machine-made sand with a fineness modulus of 2.3-2.9 and a mud content of 0.3-1%.

[0140] The preparation method comprises the following steps:

[0141] Weigh the raw materials according to their mass fractions, mix cement, coarse aggregate, fine aggregate, fly ash, silica fume and modified polypropylene fiber, add 50% of the water in the raw materials, stir for 3 minutes, then add water-based modified epoxy resin, polycarboxylate water reducer and all the remaining water in the raw materials to the system, continue stirring for 3 minutes, pour, vibrate and compact, remove the formwork 56 hours after the pouring is completed, and cure to obtain impact-resistant modified mirror concrete;

[0142] The water-based modified epoxy resin is prepared by uniformly mixing the epoxy resin emulsion and the modified curing agent 10 minutes in advance.

[0143] Comparative Example 1

[0144] Compared with Example 3, the difference is that the water-based modified epoxy resin is prepared by Comparative Preparation Example 1.

[0145] Comparative Example 2

[0146] Compared with Example 3, the difference is that the water-based modified epoxy resin is prepared by Comparative Preparation Example 2.

[0147] Comparative Example 3

[0148] Compared with Example 3, the difference is that the modified polypropylene fiber is prepared by Comparative Preparation Example 3.

[0149] Comparative Example 4

[0150] Compared with Example 3, the difference is that the modified polypropylene fiber is prepared by Comparative Preparation Example 4.

[0151] Comparative Example 5

[0152] Compared with Example 3, the difference is that the modified polypropylene fiber is prepared by Comparative Preparation Example 5.

[0153] Test Example 2

[0154] The performance of the impact-modified mirror concrete prepared in Examples 1-3 and Comparative Examples 1-5 was tested. The compressive strength of the concrete specimens was tested after curing in accordance with the national standard GB / T 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete". The impact resistance of the concrete specimens was tested in accordance with CECS 13:2009 "Test Methods for Fiber Concrete". The test results are shown in Table 2:

[0155] Table 2

[0156]

[0157] As can be seen from Table 2, the impact-resistant modified mirror concrete prepared in Examples 1-3 has good impact resistance and compressive resistance, indicating that the water-based modified epoxy resin and modified polypropylene fiber of the present invention can more effectively improve the mechanical properties of the mirror concrete.

[0158] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A modified mirror concrete, characterized in that: The invention comprises the following raw materials in parts by weight: 90-150 parts of water-based modified epoxy resin, 270-320 parts of cement, 500-600 parts of coarse aggregate, 700-800 parts of fine aggregate, 20-40 parts of silica fume, 40-60 parts of fly ash, 3-7 parts of polycarboxylic acid water reducer, 10-15 parts of modified polypropylene fiber, and 120-180 parts of water; the water-based modified epoxy resin is prepared by esterifying 2,4-diaminophenol and m-aminobenzoic acid, performing Fries rearrangement, intercalating bentonite, and mixing the mixture with the water-based epoxy resin emulsion; the modified polypropylene fiber is prepared by polymerizing and cross-linking maleic anhydride-grafted polypropylene and a silane coupling agent-modified ZnO / TiO2 nanocomposite; The preparation method of the water-based modified epoxy resin is as follows: S1. 2,4-diaminophenol and m-aminobenzoic acid are dissolved in an organic solvent, a catalyst is added, and the reaction is heated under reflux with stirring to obtain an ester; S2. The esterified product was dissolved in polyphosphoric acid, heated and stirred to obtain a curable UV absorber; S3. The bentonite was added to water, a curing UV absorber was added, and the intercalation was stirred to obtain a modified curing agent; S4. The epoxy resin, diethanolamine, ethyl bromide were stirred and mixed, heated and evaporated, and the pH value was adjusted with acetic acid to obtain an epoxy resin emulsion A; S5. The epoxy resin emulsion A and the epoxy resin were added to water and the solid content was adjusted to obtain an epoxy resin emulsion B; S6. When preparing the modified mirror concrete, the epoxy resin emulsion B and the modified curing agent were mixed uniformly to obtain a water-based modified epoxy resin; The preparation method of the modified polypropylene fiber is as follows: T1 maleic anhydride grafted modified polypropylene: maleic anhydride, polypropylene, and an initiator were added to an internal mixer, heated and stirred to blend, the product was removed, and dried to obtain maleic anhydride grafted modified polypropylene; T2. Preparation of ZnO / TiO2 nanocomposites: Zinc acetate and tetrabutyl titanate were dissolved in ethanol, citric acid and water were added, the pH of the solution was adjusted, the reaction was stirred, centrifuged, washed, dried, and calcined to obtain a ZnO / TiO2 nanocomposite. T3. Preparation of modified ZnO / TiO2 nanocomposites: The ZnO / TiO2 nanocomposites were added to an ethanol aqueous solution, a composite silane coupling agent was added, the mixture was heated and stirred, the reaction was centrifuged, washed, and dried to obtain a modified ZnO / TiO2 nanocomposite; T4. Maleic anhydride grafted modified polypropylene, modified ZnO / TiO2 nanocomposite, divinylbenzene, and initiator were added to an internal mixer, heated and stirred to react, and the product was removed and dried to obtain modified polypropylene fiber.

2. The modified mirror concrete according to claim 1, characterized in that The mass ratio of 2,4-diaminophenol, m-aminobenzoic acid, and catalyst in step S1 is 11.2-13.6:12.3-15.1:0.1-0.9, the catalyst is p-toluenesulfonic acid, and the heating, reflux, and stirring reaction time is 4-6 hours; the polyphosphoric acid in step S2 is a polyphosphoric acid having a phosphorus pentoxide content of 76-85%.

3. The modified mirror concrete according to claim 1, characterized in that The mass ratio of the bentonite and the curing ultraviolet absorber in step S3 is 10:2-3; the mass ratio of the epoxy resin, diethanolamine and ethyl bromide in step S4 is 10-15:3-6:1-3.

4. The modified mirror concrete according to claim 1, characterized in that In step S5, the mass ratio of the epoxy resin emulsion A to the epoxy resin is 3-5:13-16, and the adjusted solid content is 45-55%; in step S6, the mass ratio of the epoxy resin emulsion B to the modified curing agent is 10:4-6.

5. The modified mirror concrete according to claim 1, characterized in that In step T1, the mass ratio of maleic anhydride, polypropylene, and initiator is 3-5:15-20:0.05-0.1, the temperature of the heating and stirring blending is 160-170° C., the time is 4-6 hours, and the initiator is benzoyl peroxide; in step T2, the mass ratio of zinc acetate, tetrabutyl titanate, and citric acid is 2-4:3-7:3-5, the pH value of the solution is adjusted to 5-6, the stirring reaction time is 3-5 hours, and the calcination temperature is 450-550° C., and the time is 2-4 hours.

6. The modified mirror concrete according to claim 1, characterized in that In step T3, the mass ratio of the ZnO / TiO2 nanocomposite and the composite silane coupling agent is 10:2-3, the composite silane coupling agent includes KH602 and KH570 in a mass ratio of 3-5:2-4, the temperature of the heating and stirring reaction is 40-50°C, and the time is 2-3h; in step T4, the mass ratio of the maleic anhydride grafted modified polypropylene, the modified ZnO / TiO2 nanocomposite, divinylbenzene and the initiator is 18-22:3-5:0.5-1:0.05-0.1, the initiator is benzoyl peroxide, the temperature of the heating and stirring reaction is 160-170°C, and the time is 2-3h.

7. The modified mirror concrete according to claim 1, characterized in that The coarse aggregate is basalt with a particle size of 5-10 mm, the fine aggregate is machine-made sand with a fineness modulus of 2.3-2.9 and a mud content of 0.3-1%; and the cement is silicate cement with a PO4 of 2.

5.

8. A method for preparing the modified mirror concrete according to any one of claims 1 to 7, characterized in that: The following steps are involved: Weigh the raw materials according to their mass fractions, mix cement, coarse aggregate, fine aggregate, fly ash, silica fume and modified polypropylene fiber, add 40-60% of the water in the raw materials, stir for 2-4 minutes, then add water-based modified epoxy resin, polycarboxylate water reducer and all the remaining water in the raw materials to the system, continue stirring for 2-4 minutes, pour, vibrate and compact, remove the formwork 48-72 hours after the pouring is completed, and cure to obtain impact-resistant modified mirror concrete; The water-based modified epoxy resin is prepared by uniformly mixing the epoxy resin emulsion B with the modified curing agent 10-15 minutes in advance.

Citation Information

Patent Citations

  • Anti-cracking floor coating and preparation method thereof

    CN114410173A

  • Marble-imitated light mirror concrete and preparation method thereof

    CN115838270A